Influence of injection timing on the exhaust emissions of a dual-fuel CI engine - SAYIN, CENK (PERGAMON-ELSEVIER SCIENCE LTD, 2008)
Environmental concerns and limited amount of petroleum fuels have caused interests in the development of alternative fuels for internal combustion (IC) engines. As an alternative, biodegradable, and renewable fuel, ethanol is receiving increasing attention. Therefore, in this study, influence of injection timing on the exhaust emission of a single cylinder, four stroke, direct injection, naturally aspirated diesel engine has been experimentally investigated using ethanol blended diesel fuel from 0% to 15% with an increment of 5%. The engine has an original injection timing 27 degrees CA BTDC. The tests were performed at five different injection timings (21 degrees, 24 degrees, 27 degrees, 30 degrees, and 33 degrees CA BTDC) by changing the thickness of advance shim. The experimental test results showed that NOx and CO2 emissions increased as CO and HC emissions decreased with increasing amount of ethanol in the fuel mixture. When compared to the results of original injection timing, at the retarded injection timings (21 degrees and 24 degrees CA BTDC), NOx and CO2 emissions increased, and unburned HC and CO emissions decreased for all test conditions. On the other hand, with the advanced injection timings (30 degrees and 33 degrees CA BTDC), HC and CO emissions diminished, and NOx and CO2 emissions boosted for all test conditions. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: diesel engine; ethanol; emissions; injection timing; alternative fuel; PERFORMANCE; COMBUSTION; ETHANOL